Popular Justice or Why Were There No Sans-Culottes in America? - Dobrowolski, Paweł T. (Kwartalnik Historyczny, 2017)
The article applies a comparative perspective to assess the onset of the two ‘successful’ eighteen-century revolutions – the American and the French. The Boston events of March 1770 are compared with those of Paris in July 1789: in both cases ‘the people’ faced the soldiers, riots and politically generated violence led to bloodshed, but the subsequent actions of the insurgents showed a marked difference in understanding the sense of justice and the ways of promoting revolutionary discourse. Boston patriots relied on the English-based system of common law, were ready to condemn their own radicals and did not wish plebeian justice to prevail. They hoped for a perestroika, not for a revolution. The French – finding no culprits to condemn, and having as of yet no legal institutions of their own to use – were willing to disregard the legal continuity of the state and to search for more radical solutions.